Update on irritant-induced occupational asthma. Issue 2 (2nd April 2023) - Ronsmans, Steven; Le Moual, Nicole; Dumas, Orianne
Abstract : Purpose of review: In this narrative review, we aim to highlight novel research findings on both acute/subacute irritant-induced asthma (IIA) and chronic exposure IIA (also called 'low dose' IIA). Recent findings: Novel case series showed that acute and subacute IIA cases had similar causal agents (e.g., acid or base aerosols/fumes, dusts, mixtures) but had occurred in different circumstances (accidents vs. regular work). Acute and subacute IIA cases had similar clinical characteristics but poorer short-term outcomes than sensitizer-induced occupational asthma patients. Novel large epidemiological studies reported associations between chronic occupational exposure to irritants and current adult-onset asthma and poor asthma control, and with a specific asthma endotype characterized by neutrophilic inflammation and oxidative stress. Recent studies reconfirmed the association of the use of disinfectants and cleaning products (especially sprays) with IIA. A role for genetic susceptibility has been suggested. Summary: Recent literature provided further understanding of both acute/subacute and chronic exposure IIA, in terms of causes, possible mechanisms, and consequences such as poor asthma control. Research is needed to clarify several aspects of IIA, including its frequency (still likely underestimated), modulating factors, and mechanisms. Research aiming at improving irritant exposure assessment, including intensity/duration, and determining relevant exposure windows would be welcome.